2021
DOI: 10.1088/2057-1976/ac240b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible electroporation study of realistic normal and cancerous cervical cells model using avalanche transistor-based nano pulse generator

Abstract: In this paper, we study the reversible electroporation process on the normal and cancerous cervical cell.The 2D contour of the cervical cells is extracted using image processing techniques from the Pap smear image. The conductivity change in the cancer cell model has been used to differentiate the effects of the high-frequency electric field on normal and cancerous cells. The cells modulate themselves when this high-frequency pulse is applied based on the Debye relaxation relation. In order to computationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This work begins by extracting the scattered, overlapping, and isolated contours from the EDF images of the cervical cells with image processing tools such as GMM, MSER, and joint-level set optimization. In our earlier work, we worked on single cervical cells and successfully extracted the contour [28]. The cells extracted for electroporation study have been reported in which scattered, isolated, and sparse neuroblastoma cells have been extracted successfully and electroporation multi-physics has been analyzed [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This work begins by extracting the scattered, overlapping, and isolated contours from the EDF images of the cervical cells with image processing tools such as GMM, MSER, and joint-level set optimization. In our earlier work, we worked on single cervical cells and successfully extracted the contour [28]. The cells extracted for electroporation study have been reported in which scattered, isolated, and sparse neuroblastoma cells have been extracted successfully and electroporation multi-physics has been analyzed [16].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a feasible mechanism that employs reversible electroporation for modulating dye uptake in cells. The experimental schematic employs a low-cost and simple nano-pulse generator, that has already been proposed [28]. We have been able to introduce a microdosimetry model in which a reversible electroporation study under a nanosecond pulse for the realistic contour of isolated, overlapping and scattered cervical cells was done and introduction of mathematical dye delivery equation into the simulation work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations